POLA PEMANFAATAN ARTIFICAL INTELLIGENCE DALAM PEMBELAJARAN QIRA’AH MUWASSA’AH: STUDY KASUS MAHASISWA PENDIDIKAN BAHASA ARAB - Hidayah, Maslahatul; Umar Faruq; Ahmad Yasin Mustofa; Hasim Ashari; Adis Mulyadi; Rian (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of Artificial Intelligence (AI) has significantly influenced learning processes in higher education, including Arabic language learning. This study aims to describe students' tendencies in utilizing Artificial Intelligence in Qirā'ah Muwassa'ah learning and to identify the benefits and challenges arising from its use. The study employed a qualitative approach with a case study design. The participants consisted of 18 fourth-semester students of the Arabic Language Education Department at UIN Syekh Wasil Kediri. Data were collected through observation and questionnaires and analyzed using the Miles, Huberman, and Saldaña model, which includes data condensation, data display, and conclusion drawing. The findings revealed that students utilized AI to translate vocabulary, comprehend reading texts, obtain additional information, and prepare presentation materials. The questionnaire results indicated that the level of AI utilization reached 74.52%, which falls into the good category. The study identified two major tendencies: the use of AI as a learning support tool and the use of AI as the primary source of understanding. Although AI provides various benefits in improving learning efficiency and reading comprehension, excessive reliance on AI may lead to dependency and reduce students' engagement in critical thinking processes. Therefore, the integration of AI in Qirā'ah Muwassa'ah learning should be directed as a supportive learning tool that promotes critical reading skills and learner autonomy.